2021
DOI: 10.1111/vsu.13605
|View full text |Cite
|
Sign up to set email alerts
|

Zürich cementless total hip arthroplasty as a treatment option for capital physeal fractures in dogs: Outcome in 53 cases

Abstract: Objective To review the outcome of dogs that underwent Zürich cementless total hip arthroplasty (Z‐THA) for the repair of acute and chronic capital physeal fractures (CPF) and document the CPF‐related hip remodeling. Study design Retrospective study. Sample population Fifty‐three Z‐THA in 53 dogs. Methods Medical records of dogs (2006‐2019) that underwent Z‐THA for CPF management were reviewed. Dogs were divided into two groups on the basis of the days elapsed between CPF diagnosis and Z‐THA, acute (≤30 days) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The lack of association of trochanter grade and underlying diagnosis was noteworthy. A recent study described a high incidence of medialization of the trochanter in dogs with chronic capital physeal fractures (range: 45–2920 days) treated with a non-press fit cementless THR system [ 40 ]; however, that study contained some cases with fractures of several years duration prior to THR, and cases were not evaluated in the context of other pathologies of the hip as was performed in the present study. Additionally, the study by Alvarez-Sanchez and colleagues assessed trochanter position using a THR system-specific “25° of supination” lateral femoral radiograph, whereas in the present study trochanter grade was determined from traditional craniocaudal radiographs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of association of trochanter grade and underlying diagnosis was noteworthy. A recent study described a high incidence of medialization of the trochanter in dogs with chronic capital physeal fractures (range: 45–2920 days) treated with a non-press fit cementless THR system [ 40 ]; however, that study contained some cases with fractures of several years duration prior to THR, and cases were not evaluated in the context of other pathologies of the hip as was performed in the present study. Additionally, the study by Alvarez-Sanchez and colleagues assessed trochanter position using a THR system-specific “25° of supination” lateral femoral radiograph, whereas in the present study trochanter grade was determined from traditional craniocaudal radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Alvarez-Sanchez and colleagues described the pre-operative radiographic abnormalities and outcomes in dogs with capital physeal fractures treated with a cementless THR system. The position of the greater trochanter was radiographically assessed for medial overhang relative to the central axis of the medullary canal on oblique lateral radiographs in 25° of supination, which is unique radiographic projection to the cementless THR system used in that study [ 40 ]. Therefore, the objectives of the present study were to classify frontal plane greater trochanter morphology using traditional radiographic views in a cohort of dogs undergoing cementless THR and to identify potential associations between trochanter morphology and patient demographics, femoral geometry, surgical time, technique modifications, and post-operative stem position.…”
Section: Introductionmentioning
confidence: 99%
“…1 2 3 4 5 Indications for THA include coxofemoral subluxation and luxation, chronic osteoarthritis, fractures of the femoral head and neck, avascular necrosis of the femoral head and revision of femoral head and neck ostectomy. 1 2 3 5 6 7 8 9 10 11 Prior studies evaluating the clinical outcome of THA in dogs have reported a complication rate ranging from 4 to 34%. 1 2 3 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 Postoperative luxation is the most widely reported complication of THA, occurring in 1 to 20% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…1 2 3 5 6 7 8 9 10 11 Prior studies evaluating the clinical outcome of THA in dogs have reported a complication rate ranging from 4 to 34%. 1 2 3 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 Postoperative luxation is the most widely reported complication of THA, occurring in 1 to 20% of cases. 2 6 13 15 19 21 24 25 26 27…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation